2017
DOI: 10.1097/gox.0000000000001419
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Are Better after Oncoplastic Breast Conservation than after Mastectomy and Autologous Reconstruction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 41 publications
0
28
1
1
Order By: Relevance
“…With the rise of reconstructive surgery, aesthetic satisfaction has become an important factor influencing patient decision making when considering surgical treatment choices for breast cancer removal [22]. Although both M+R and OS inherently represent reconstructive techniques, OS has higher patient satisfaction [19, 20] and has also been shown to be cost-effective [23, 24]. Collectively, these fundamental principles may influence a patient’s decision for breast reconstruction, and thereby explain the trends seen in our present analysis [6, 12].…”
Section: Discussionmentioning
confidence: 99%
“…With the rise of reconstructive surgery, aesthetic satisfaction has become an important factor influencing patient decision making when considering surgical treatment choices for breast cancer removal [22]. Although both M+R and OS inherently represent reconstructive techniques, OS has higher patient satisfaction [19, 20] and has also been shown to be cost-effective [23, 24]. Collectively, these fundamental principles may influence a patient’s decision for breast reconstruction, and thereby explain the trends seen in our present analysis [6, 12].…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, limited high‐quality comparative evidence to support the benefits of TM as an alternative to mastectomy with or without IBR. Single‐centre case series have suggested that, overall, patients undergoing TM may report better quality of life than those undergoing mastectomy and IBR. There is emerging evidence to suggest that TM may be a cost‐effective alternative to mastectomy and immediate implant‐based and free‐flap reconstruction in a North American setting.…”
Section: Introductionmentioning
confidence: 99%
“…Breast reconstruction (OPS or M + R) offers patients an improved quality of life by providing an aesthetically symmetric breast together with higher patient satisfaction [2,3,4]. Unfortunately, complication rates persist in breast cancer surgery and vary (2–40%) with the type of reconstruction.…”
Section: Introductionmentioning
confidence: 99%